2006
DOI: 10.1021/ja060084x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Gold Atom Penetration through Alkanethiolate Self-Assembled Monolayers on Au{111} by Adjusting Terminal Group Intermolecular Interactions

Abstract: The penetration behavior of thermally evaporated Au on S(CH(2))(15)CH(3), S(CH(2))(15)CO(2)CH(3), S(CH(2))(15)CO(2)H, K-modified S(CH(2))(15)CO(2)CH(3), and K-modified S(CH(2))(15)CO(2)H self-assembled monolayers (SAM) on Au substrates is investigated. Gold is a particularly interesting metal since vapor-deposited Au atoms are known to pass through alkanethiolate SAMs on Au{111} substrates at room temperature. Here we show that it is possible to control Au penetration by adjusting the interactions between term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 67 publications
3
71
0
Order By: Relevance
“…[10,75] Interactions between end groups of the molecular layer and deposited metals have also been reported for Cu on porphyrin monolayers [84,147] and on SAMs. [130,[148][149][150][151] Notably, particular end-group/top contact metal combinations can yield a chemical association that reduces metal penetration into the monolayer. [150,151] An FTIR study of aromatic monolayers bonded to Si via SiÀC bonds derived from diazonium reduction reported that soft deposition of 100 nm of Au produced minor perturbations of the IR spectrum, while direct e-beam deposition of the same thickness caused serious degradation of the aromatic structure of the monolayer.…”
Section: Progress Reportmentioning
confidence: 99%
“…[10,75] Interactions between end groups of the molecular layer and deposited metals have also been reported for Cu on porphyrin monolayers [84,147] and on SAMs. [130,[148][149][150][151] Notably, particular end-group/top contact metal combinations can yield a chemical association that reduces metal penetration into the monolayer. [150,151] An FTIR study of aromatic monolayers bonded to Si via SiÀC bonds derived from diazonium reduction reported that soft deposition of 100 nm of Au produced minor perturbations of the IR spectrum, while direct e-beam deposition of the same thickness caused serious degradation of the aromatic structure of the monolayer.…”
Section: Progress Reportmentioning
confidence: 99%
“…Potential changes to consider include distortions of the S-Au binding configuration, and displacement of gold atoms, including formation of metal filaments as proposed by some authors [37].…”
Section: The Two-path Modelmentioning
confidence: 99%
“…Nanofabrication results in junctions able to trap a much smaller number of molecules: the evaporation of gold through a nanopore mask on top of a SAM reduces the area of the junction to less than 300 mm 2 , and therefore reduces the probability of incorporating defects in the junctions (but also the current). Although these systems have demonstrated interesting functionalities, there has been little characterization (Zhu et al 2006;Walker et al 2007) of the nature of the interface formed by the evaporation of metal atoms onto organic films, and electrical shorts due to the percolation of Au atoms through the film (and probably other types of defects) have limited the reproducibility of the results.…”
Section: Tools For the Study Of Charge Transport Through Organic Molementioning
confidence: 99%